Analisis Kendala Pelaksanaan Pembelajaran Daring Pada Kompetensi Keahlian Teknik Instalasi Tenaga Listrik - Lara Widya Astuti; Hansi Effendi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to determine the obstacles to implementing online learning for students of Electrical Power Installation Engineering Skills Competence at the Adi Karya Ranah Pesisir Technology Vocational School. The research method used is a descriptive method and a survey with a quantitative approach, data collection techniques using a questionnaire sent via Whatsapp Group messages. The data analysis technique used descriptive statistics using the percentage formula. The results showed that the obstacles to the implementation of online learning could be categorized as not constrained. Of the five indicators discussed in the statement in the questionnaire distribution, including the subject matter indicator is not constrained, the discussion material indicator is not constrained, the device indicator is constrained, the learning application indicator is not constrained, the data and network indicator is constrained the learning evaluation indicator is not constrained .